2011
DOI: 10.1186/1475-2875-10-301
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of malaria prevalence in two Indian cities using the response surface method

Abstract: BackgroundElucidation of the relationships between malaria incidence and climatic and non-climatic factors in a region is of utmost importance in understanding the causative factors of disease spread and design of control strategies. Very often malaria prevalence data is restricted to short time scales (months to few years). This demands application of rigorous statistical modelling techniques for analysis and prediction. The monthly malaria prevalence data for three to five years from two cities in southern I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Thus Malaria-incidence may be inaccurate due to limited health-care resources [43] or wrong population-size [47]. To plan public-health interventions, estimation of malaria burden is a necessary requirement, for which SPR may be used as a surrogate measure for malaria-incidence [43,45,48,49], to express the quantum of malaria endemicity in any region [47], plus to identify high risk areas [50]. In annual reporting system, Annual Parasite Index (i.e., malaria-incidence rate) is the principal monitoring indicator in malaria control programme in Kolkata for several years [50,52].…”
Section: Resultsmentioning
confidence: 99%
“…Thus Malaria-incidence may be inaccurate due to limited health-care resources [43] or wrong population-size [47]. To plan public-health interventions, estimation of malaria burden is a necessary requirement, for which SPR may be used as a surrogate measure for malaria-incidence [43,45,48,49], to express the quantum of malaria endemicity in any region [47], plus to identify high risk areas [50]. In annual reporting system, Annual Parasite Index (i.e., malaria-incidence rate) is the principal monitoring indicator in malaria control programme in Kolkata for several years [50,52].…”
Section: Resultsmentioning
confidence: 99%
“…Existing regression or other mathematical forecasting models forecasted the malaria transmission in Africa 26 27 and in India 28 29 30 in one month advance using climatic variables such as rainfall and temperature. India has diversified climatic characteristics; therefore, implementation of climate-based model for the whole country is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria outbreaks generally occur due to unexpected rainfall, resistance in vector and parasite towards insecticide and drugs, respectively 30 31 , migration, inadequate intervention, etc . The statistical method of mean+2 SD for detecting outbreak could detect major outbreaks in Karbi Anglong district but not the minor outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge for malaria epidemiologists is to evaluate the strengths and weaknesses of both methods in estimating malaria incidence and time trends, especially as malaria control programmes are intensified worldwide [14][15][16][17][18][19][20][21] . Malaria is endemic in Mangalore, India which is rapidly undergoing industrialization, witnessing an unprecedented spurt in construction activities in recent years, thus facing the problem of mosquito breeding in man-made clear water sources like wells, overhead tanks, sumps, cisterns as well as other defective and illegal drainage systems 22 . It is observed that the number of cases belonged to migratory labors showing less resistance to malarial infection when compared to the local population, so it was difficult for us to discriminate the number of positive cases among migratory labor and local population as the occupational history in the record was not properly entered.…”
Section: Discussionmentioning
confidence: 99%